Isolation and characterization of halotolerant bacteria from soils in the municipality of Remedios, Cuba - Ortega-Garcia, Marisel; Ríos-Rocafull, Yoania; Tejeda-González, Grisel; Zelaya-Molina, Lily; Chávez-Díaz, Ismael; Nápoles-García, María (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2026)
The isolation of halotolerant bacteria represents a strategy to mitigate soil salinization and promote crop adaptation. This study aimed to identify bacteria from saline soils in Remedios, Cuba, and evaluate their potential as plant growth-promoting bacteria (PGPB). Three bacterial strains tolerant to 200 mM NaCl were selected and identified as Proteus sp. RM 4.2, Lysinibacillus sp. RM 6.2, and Tenebrionicola sp. RM 4.1. The three strains showed the ability to fix nitrogen and produce siderophores and lytic enzymes. In tomato plant inoculation assays, Proteus sp. RM 4.2 significantly promoted plant growth in the evaluated cultivars, standing out as the strain with the greatest growth-promoting effect. Overall, the results indicated that the evaluated strains exhibited functional traits associated with plant growth promotion and represented a viable alternative for developing bioinoculants in saline soils.